Strutture poetologiche nel Woyzeck di Georg Büchner - Furlani, Simone (Itinerari, 2024)
Georg Büchner’s polemic against Romanticism, against what he calls “ideal art”, fits perfectly into the perspective of the “end of art” proclaimed by Hegel. This is not, of course, to affirm the impossibility of art, but rather the need for art to reflect on itself and deconstruct its abstractness. This essay, focusing on Woyzeck (1836-37), highlights the structures that enable Büchner to articulate his realism. These are reflexive (poetological) structures that involve a demystification of art (of theater, literature, etc.) and a self-subtraction to let reality emerge, a deconstruction of self that also concerns language, and the text that structures the drama. It is at the level of this reflexivity of art that the problem and a particular rendering of the relationship between philosophy and literature, between thought and artistic language, opens up. The tension between reality and immanence in the real, to which Büchner’s work gives substance, thus moves forward within the perspective opened by Hegel, to the point of prefiguring some philosophical elements that will later be found institutionalized in Nietzsche’s thought.